Spatial Resolution of Suprachoroidal–Transretinal Stimulation Estimated by Recording Single-Unit Activity From the Cat Lateral Geniculate Nucleus - Miyoshi, Tomomitsu; Morimoto, Takeshi; Sawai, Hajime; Fujikado, Takashi (Frontiers in Neuroscience, 2021)
Retinal prostheses are devices used to restore visual sensation in patients suffering from photoreceptor degeneration, such as retinitis pigmentosa. Suprachoroidal-transretinal stimulation (STS) is a prosthesis with retinal electrodes located in the sclera. STS has the advantage that it is safer than epiretinal or subretinal prostheses, as the implant is not directly attached to the retinal tissue. We have previously reported feasibility of STS with animal experiments and clinical trials. However, functional evaluation with neurophysiological experiments is still largely missing. To estimate the spatial resolution of STS, single-unit activities in response to STS were recorded from relay cells in the dorsal lateral geniculate nucleus of cats, and the response probability of the units was analyzed in relation to the distance between the stimulus location and the receptive field of each recorded unit. A platinum electrode was attached to the sclera after lamellar resection, and the return electrode was placed in the vitreous. The stimulating current, which ranged from 50 µA to 500 µA, was applied between these electrodes, and the probability of spike responses occurring just after retinal stimulation was measured. The distance at half-maximum of response was determined from the collected response probabilities as a function of stimulus intensity for all units characterized by their distances from the receptive field center to the stimulation point. As the stimulation became weaker, this distance decreased to 1.8 degrees at 150 and 100 µA. As another estimation, the radius of 25% response probability was 1.4 degrees at 100 µA. The diameter of the stimulated cat retinal area, 3.6 or 2.8 degrees, corresponds to human visual acuity of 0.005 or 0.007, or finger counting. Considering the lower hazard to the retina of STS and its potentially large visual field coverage, STS is an attractive method for retinal prosthetic device development.